Rates of return to education of blacks in South Africa - Serumaga-Zake, Philip A (Rhodes University, Faculty of Science, Department of Statistics, 1991)
The principal objectives of this empirical study were to test the hypothesis that eduction is a major determinant of people's earnings differentials and to calculate private and social rates of return to education of blacks in South Africa excluding Transkei, Bophuthatswana, Venda and Ciskei. Basically, the data for working men and women used in the study were extracted from the 1985 current Population survey files comprising a sample representative of the black population. Lifetime earnings profiles are constructed from these data for five educational levels, namely, no schooling up to standard 1, standards 2 to 4, standards 5 to 7, standards 8 to 9 and standard 10. Schooling is assumed to account for 60% of the income differentials between these profiles, after adjustment for the differing probabilities of finding work of persons in specific age-education groups. Imputed average household outlays on schooling are taken as the private direct cost of education supplemented by estimates of per pupil spending by the various government departments responsible for black schooling for calculation of the social costs per year of primary and secondary schooling. Indirect cost in the form of imputed foregone earnings are included from standard 5 (age 15) onwards. The resulting private internal rates of return to education of males are about 16% at primary level and 24% for secondary schooling. Corresponding social rates of return are about 6% for primary and 15% for secondary education. The estimates for females indicate that between no schooling and standards 2 to 4 level, the private and social rates of return are -1% and -4% respectively, from standards 2 to 4 to standards 5 to 7 level, private returns of 12% and social returns of 4% are reported and for the remaining secondary school phases private returns of 32% and social returns of 15% are estimated. It is implied that black education is receiving minimal government financial assistance compared to those of the other population groups. The evidence of the results of the study indicates that; besides education, marital status, locational, regional and occupational variables also influence earnings differentials, the governments responsible for black education should emphasize human capital investment in relation to physical capital investment, on average more educated persons are better off than the less educated ones and with the exception of female early primary schooling, generally, it is worthwhile for an individual to undertake a certain educational programme investment
Keywords: Black people -- Education -- South Africa -- Statistics; Black people -- Employment -- South Africa -- Statistics; Black people -- South Africa -- Economic conditions -- Statistics